Unveiling Factors and Strategies to Alleviate Anxiety Among EFL Student Teachers in Online and In-Person Practicums - Ramazan Yetkin; Nuray Alagözlü (SAGE Open)
The role of anxiety in language education has been well established as a significant factor affecting the success or failure of both teachers and students, including student teachers (STs). While there is a substantial body of research examining student-teacher anxiety (STA), particularly within in-person practicum settings, most of these studies have focused on assessing anxiety levels or identifying factors that induce anxiety. However, a dearth of studies remains that address coping strategies, particularly in the context of online classrooms. Therefore, this study aims to investigate anxiety factors and strategies to alleviate anxiety in both online and in-person contexts. Adopting a qualitative approach, the study involved 14 EFL STs whose experiences were documented through reflective journals and in-depth semi-structured interviews. Thematic analysis of the data revealed significant commonalities in factors and strategies across both modalities, highlighting the importance of teacher self-efficacy, student engagement, and mentor support. These findings underscore the need for tailored support mechanisms to alleviate anxiety during practicum experiences. Such mechanisms may involve leveraging diverse resources, including mentorship programs, supportive practicum schools, the integration of theoretical knowledge with practical application, and additional support beyond traditional classroom settings. By implementing these strategies, educators and institutions can better equip STs to navigate and effectively manage anxiety during their practicum experiences.